THE ROLE OF THE HEAD OF WELFARE AND SERVICE IN TOLONDADU I VILLAGE, BOLAANG UKI SUB-DISTRICT, SOUTH BOLAANG MONGONDOW DISTRICT: THE ROLE OF THE HEAD OF WELFARE AND SERVICE IN TOLONDADU I VILLAGE, BOLAANG UKI SUB-DISTRICT, SOUTH BOLAANG MONGONDOW DISTRICT - Rahmat Yamin; Siske Anani; Aryati Hamzah (Journal of Economic, Business, and Administration (JEBA), 2024)
This study aims to determine the role of the head of the welfare and service section in Tolandadu I Village, Bolaang Uki District, South Bolaang Mongondow Regency. It uses a qualitative approach, with the main focus on the quality of the analysis. This research was conducted at the Tolondadu I village office, Bolaang Uki District, South Bolaang Mongondow Regency, for two months and two weeks, from 17 April 2023 to 28 June 2023.Based on the results of research conducted in Tolondadu I Village, Bolaang Uki District, South Bolaang Mongondow Regency, regarding the study of the implementation of the main tasks and functions of the head of the welfare section in the field of welfare and community empowerment. Carrying out data collection and preparation in the field of welfare and community empowerment has not been running well and by the rules and assisted by PKK cadres and community leaders.